Euphemistic representations of death in armed criminal group eradication discourses in West Papua - Wijana, I Dewa Putu; Yoga, Adwidya (International Journal Linguistics of Sumatra and Malay, 2025)
This article is intended to describe various forms and strategies used by video clip narrators in creating death euphemistic expressions during eradication processes of Armed Criminal Group rebellion in West Papua. All data are collected from discourses of video clips narration concerning soft and hard approaches carried out by Indonesian police and Indonesian National Army. Based on careful analysis of the collected data, it is found that there are considerable differences regarding motivations between common or conventional death euphemistic expressions and ones used to described death in the separatist eradication. Most of death euphemisms found in video clips narration are motivated by ludic communicative functions of a language s be set in by the imbalance power of the two fighting parties. The linguistic forms of euphemistic expressions can be differentiated into words, phrases, and clauses. Finally, various strategies exploited to create them include figurative, remodeling, circumlocution, abbreviation, metonymy, hyperbole, and understatement.